Primary meningococcal arthritis associated with adult respiratory distress syndrome. Issue 8 (August 1990) - Samanta, A; Turner, A; Roy, S; O'Leary, A
Abstract : A previously fit and well 20 year old man with primary meningococcal arthritis of the left knee is described. Despite intensive search there was no evidence of extra-articular meningococcal infection. He subsequently developed adult respiratory distress syndrome as a rare and previously undescribed complication.